2001
DOI: 10.3748/wjg.v7.i5.722
|View full text |Cite
|
Sign up to set email alerts
|

p16 gene methylation in colorectal cancers associated with Duke’s staging

Abstract: AIM To explore the association of methylation of the CpG island in the promotor of the P16 tumor suppressor gene with the clinicopath ological characteristics of the colorectal cancers.METHODS Methylation-specific PCR (MSP) was used to detect P16 methylation of 62 sporadic colorectal cancer specimens.RESULTS P16 methylation was detected in 42% of the tumors. Dukes' staging was associated with P16 methylation status. p16 methylation occurred more frequently in Dukes' C and D patients (75.9%) than in Dukes' A an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
4
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(8 citation statements)
references
References 33 publications
3
4
1
Order By: Relevance
“…We found a significant association of the p16INK4a methylation status with higher Dukes’ stage (C+D). These results are in concordance with those of other studies ( 20 , 21 , 23 ), which have reported the same observations of a higher methylation status of p16INK4a gene promoter with higher Dukes’ stage (C+D). Duke’s staging has been considered a most significant prognostic determinant in cancers ( 20 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We found a significant association of the p16INK4a methylation status with higher Dukes’ stage (C+D). These results are in concordance with those of other studies ( 20 , 21 , 23 ), which have reported the same observations of a higher methylation status of p16INK4a gene promoter with higher Dukes’ stage (C+D). Duke’s staging has been considered a most significant prognostic determinant in cancers ( 20 ).…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, we observed hypermethylation of the p16INK4a gene promoter in 42.1% (48/114) of CRC cases, which is higher than reported by other major studies in the world ( 11 , 20 , 21 ). However, our observation is consistent with other studies ( 22 , 23 ) which have reported a similar frequency of p16INK4a hypermethylation in CRC tumours in the Japanese population.…”
Section: Discussioncontrasting
confidence: 62%
“…p16 INK4a , a product of the CDKN2/MTS1 gene located at the chromosomal region 9p21, is a negative regulator of G1/S‐phase transition that promotes cell‐cycle arrest via the Rb tumor suppressor pathway, and its expression increases along with the onset of cellular senescence 9–13 . In colorectal cancers, homozygous deletion and mutation of the CDKN2/MTS1 gene are reportedly very rare, 35–37 while methylation of the gene is detected in 18–53% of the cancer series 19,20 , 23,25 , 37 . Reportedly, inactivation of the CDKN2/MTS1 gene is generally associated with an aggressive phenotype and poor prognosis in a wide range of neoplasms, including colorectal cancers, 19,20 , 23,25 , 28 and is usually paralleled with loss or markedly reduced expression levels of p16 INK4a protein and mRNA 28,37 .…”
Section: Discussionmentioning
confidence: 99%
“…In colorectal cancers, homozygous deletion and mutation of the CDKN2/MTS1 gene are reportedly very rare, 35–37 while methylation of the gene is detected in 18–53% of the cancer series 19,20 , 23,25 , 37 . Reportedly, inactivation of the CDKN2/MTS1 gene is generally associated with an aggressive phenotype and poor prognosis in a wide range of neoplasms, including colorectal cancers, 19,20 , 23,25 , 28 and is usually paralleled with loss or markedly reduced expression levels of p16 INK4a protein and mRNA 28,37 . In the present immunohistochemical investigation, p16 INK4a expression was low in 68% of the resected tumors in the untreated control patients and in 71% of the preoperative biopsy specimens.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation